Comparison of staphylococcal coagglutination, latex agglutination, and counterimmunoelectrophoresis for bacterial antigen detection. - Thirumoorthi, M C (1979)
Soluble antigens of Haemophilus influenzae type b, Streptococcus pneumoniae, Neisseria meningitidis, and group B streptococcus were looked for in cerebrospinal fluid, serum, and urine by using the staphylococcal coagglutination test, latex agglutination test, and counterimmunoelectrophoresis. The staphylococcal coaggultination and latex agglutination tests were more sensitive than counterimmunoelectrophoresis in identifying antigens of H. influenzae type b, S. pneumoniae, and N. meningitidis. None of the three tests successfully detected group B streptococcal antigens in body fluids. Nonspecific reactions noted with the staphylococcal coagglutination test could be usually eliminated after premixing test specimens with soluble protein A.